Proper use of the cluster analysis in plant germplasm characterization. - Núñez-Colín, Carlos Alberto (2011)
The present essay aims to make a recompilation of basic information to properly perform the cluster analysis. This multivariate method allows making groups and it is widely used in studies of genetic resourcescharacterization. It is mentioned topics like the data typesto use, similarity and dissimilarity indices, agglomerativemethods, and the correct way to establish the number ofgroups into a dendrogram.